6(x+10)-2(2x+30)=40

Simple and best practice solution for 6(x+10)-2(2x+30)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+10)-2(2x+30)=40 equation:


Simplifying
6(x + 10) + -2(2x + 30) = 40

Reorder the terms:
6(10 + x) + -2(2x + 30) = 40
(10 * 6 + x * 6) + -2(2x + 30) = 40
(60 + 6x) + -2(2x + 30) = 40

Reorder the terms:
60 + 6x + -2(30 + 2x) = 40
60 + 6x + (30 * -2 + 2x * -2) = 40
60 + 6x + (-60 + -4x) = 40

Reorder the terms:
60 + -60 + 6x + -4x = 40

Combine like terms: 60 + -60 = 0
0 + 6x + -4x = 40
6x + -4x = 40

Combine like terms: 6x + -4x = 2x
2x = 40

Solving
2x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '2'.
x = 20

Simplifying
x = 20

See similar equations:

| (2x-5)=(2x+6) | | 17s=221 | | 3/4÷9 | | 3-1(2y+-5)=7-2(y+1) | | 52v=156 | | 6÷1/2 | | 6(x+10)-2(3x+30)=40 | | 6(x+10)-2(3x+30)=4x-10 | | 26+10p=36+8p | | 5x+4=289 | | 6(k+8)+7k=-8 | | 8(-0.5+-0.375x)+4=-3x | | -9(t+6)=18 | | f(x)=20+40 | | 4x=18x | | -2(3t-5)+3t=2t-2 | | 6(x+36)-3(2x+12)=4x-10 | | x^2-14y=0 | | 5b-b=8 | | 3x(5-2x)+4=6 | | 7/12=7/9x | | (1-3x)=-8x+14 | | 2/n=-7 | | 20=a+3 | | x^2=-5y | | 8(x-4)+4(x-8)+(x-3)=2x-1 | | 66+6y-20=16y-10-2y | | Z^3+5z+3z^2+1+4-2z^2= | | 24/25=s/35 | | -10/9i | | 4(n+6)=8-4(n-2) | | 12+p=8+7 |

Equations solver categories